DIFFERENCES IN THE EFFECTS OF SMALL SIDED GAMES AND RONDO TRAINING ON FUTSAL PASSING ACCURACY OF PS UNMER MALANG CITY PLAYERS - Prasetyo, Chandra Tri Hidayat; Pribadi, Heri Purnama (Indonesian Conditioning Coaches, 2025)
Training is aimed at improving an athlete's abilities in a methodical and consistent manner to demonstrate their peak performance. This specifically refers to training focused on passing. Small Sided Games serve as a training technique used in futsal that closely mimics a real match scenario, with modifications in aspects such as rules, playing area, and number of participants. These games revolve around skill development and conditioning, serving as game-oriented drills. They offer an efficient way to train that addresses technique, strategy, and physical endurance all at once. The method used in this study was a quasi-experimental study with two groups, namely, experimental group 1 which was given small-sided games training and experimental group 2 which was given rondo training which was selected randomly. The population was studied 25 players with 22 players selected as research samples through purposive sampling techniques. This study shows that there are changes resulting from both exercises on the passing accuracy of the players. The conclusion is that small sided games and rondo training both have an influence on passing in each group.